Ефективність хірургічного лікування хворих з І-ІІ стадіями недрібноклітинного раку легені - Колеснік, Олексій Петрович; Колесник, А. П.; Kolesnik, O. P. (Українська медична стоматологічна академія, 2013)
Рак легенів залишається провідним онкологічним діагнозом за кількістю щорічно зареєстрованих випадків захворюваності та смертності. Операція є єдиним методом лікування, що дозволяє пацієнту отримати шанс на видужання. Однак навіть після „радикально” проведеного хірургічного втручання до 50-60% хворих гинуть від прогресування хвороби у наступні п’ять років. Метою дослідження було визначення факторів, що впливають на ефективність хірургічного лікування. Дослідження проведено кафедрою онкології Запорізького державного медичного університету з червня 2006 по грудень 2012 року. Всього у дослідження включено 254 пацієнта. Всім хворим проводили обстеження та лікування згідно національних рекомендацій з онкології. Лобектомію виконано 159 хворим, в той час як пневмонектомію провели 94 пацієнтам. Одному пацієнту проведено оперативне лікування в об’ємі атипової резекції легені. У хворих з лобектомією відмічається значно краще виживання, ніж у хворих, яким виконано пневмонектомію (р=0,007). При цьому медіана виживаності не досягнена в обох групах, однак 75-й процентіль виживаності склав 30,0±9,5 місяців у хворих яким виконано лобектомію, та 13,0±2,4 місяців у хворих після пневмонектомії. Основним фактором, що визначав об’єм оперативного втручання є локалізація пухлини. Так при центральних формах недрібноклітинного раку легені частіше виконували пневмонектомію (р<0,001), а при периферичних пухлинах – лобектомію. Ще одним фактором, що впливав на вибір виду операції був розмір пухлини. Зі збільшенням розміру пухлини підвищується вірогідність виконання пневмонектомії (р<0,001). Факторами, при яких відмічається найбільш несприятливий прогноз після виконання пневмонектомі,ї є жіноча стать хворих, ІІ стадія НДКРЛ, ІМТ <30 мг/м2, периферична локалізація новоутворення та наявність некрозів у пухлині. Рак легких остается ведущим онкологическим диагнозом по количеству ежегодно регистрируемых случаев заболеваемости и смертности. Операция является единственным методом лечения, что позволяет пациенту получить шанс на выздоровление . Однако даже после "радикально" проведенного хирургического вмешательства до 50-60% больных погибают от прогрессирования болезни в следующие пять лет. Целью исследования было определение факторов, влияющих на эффективность хирургического лечения . Исследование проведено кафедрой онкологии Запорожского государственного медицинского университета с июня 2006 по декабрь 2012 года. Всего в исследование включено 254 пациента. Всем больным проводили обследование и лечение согласно национальным рекомендациям по онкологии . Лобэктомию выполнено 159 больным, в то время как пневмонэктомию провели 94 пациентам. Одному пациенту проведено оперативное лечение в объеме атипичной резекции легкого . У больных с лобэктомия отмечается значительно лучшее выживание, чем у больных которым выполнено пневмонэктомию (р = 0,007). При этом медиана выживаемости недостигнута в обеих группах, однако 75 -й процентиль выживаемости составил 30,0 ± 9,5 месяцев у больных, которым выполнено лобэктомию, и 13,0±2,4 месяцев у больных после пневмонэктомии . Основным фактором, опре- делявшим объем оперативного вмешательства является локализация опухоли. Так при центральных формах немелкоклеточного рака легкого чаще выполняли пневмонэктомию (р< 0,001 ), а при периферических опухолях - лобэктомию . Еще одним фактором, влияющим на выбор вида операции, был размер опухоли. С увеличением размера опухоли повышается вероятность выполнения пневмонэктомии (р < 0,001 ). Факторами, при которых отмечается наиболее неблагоприятный прогноз после выполнения пневмонэктомии, является женский пол больных, II стадия НМКРЛ, ИМТ < 30 мг/м2 периферическая локализация новообразования и наличие некрозов в опухоли. Introduction: Lung cancer is the mail cause of oncology incidence and mortality. There were 17418 new cases of incidence and 13621 fatal cases registered in Ukraine in 2011. Surgery is the best method of treatment patients with lung cancer. But about 50-60% of patients experience relapse of the disease and die for five years after “radical” operation. Clinical and morphologycal factors can help distinguish patients with high risk of cancer progression after surgery. It will allow us to develop patient-centered management and to improve survival rate. Objective: survival rate of patients with І-ІІ stages of non-small cell lung cancer after surgical treatment due to clinico-morphologycal factors. Materials and Methods: Study was conducted in the chair of oncology, Zaporozhye state medical university. The clinical base was thoracal department of Zaporozhye regional clinical oncology center. The patients inclusion were from June 2008 to December 2012. It were included 254 patients. Examinations and treatment were conducted due to National Ukrainian guidelines. Lobectomy was performed for 159 patients. Pneumonectomy was conducted in 94 cases. There was one atypical resection. Results: Lobectomy was conducted in women more often than in men (р=0,008). This might result from more peripheral location of tumors in women (р=0,002), that was diagnosed by screening program (р=0,001). We also observed that lobectomy was more often performed in the patients with right lungs tumor (р<0,001). This might be due to the presence of three lobes in the right side and only two in the left one. And it was possible to perform bilobectomy for cancer spreading in two lobes in right lung cancer and only pneumonectomy in the left side. Location of the tumor was the main factor for making decision on the volume of resection. For central located tumor pneumonectomy was more often conducted than for peripheral cancers (р<0,001). Size of the malignant tumor was another factor than influenced to surgical resection. Patients with larger tumors more often had pneumonectomy (р<0,001). The better survival rate was shown by the patients after lobectomy than in patients after pneumonectomy (р=0,007). Median of survival time was not reached in both groups. But for 75 % of the patients the survival time was 30,0±9,5 months after lobectomy and 13,0±2,4 month for patients after pneumonectomyї. Body mass index (BMI) ≥30 mg/m2, improve survival patients with pneumonectomy (р=0,001). Patients with BMI <30 mg/m2 had lower survival after surgical treatment than patients with BMI ≥30 мг/м2. There were no differences of survival patients after lobectomy and pneumonectomy why had tumors size <3 cm (Т1). Metastatic lesin in lymph node of root of lung significantly worsened survival patients after lobectomy and pneumonectomy. Mediam of survival were 38,0±9,1 and 26,0 months respectively. “T”, “N” and “M” criteria create stage of disease. So, patients with a first stage of non small cell lung cancer repeated regularity as in patients with Т1 and N0 creteria. It is favorable survival after lobectomy and after pneumonectomy. Analysis of survival rate in patients with early stages of non-small cell lung cancer after surgical treatment was conducted. This analysis showed that there were no differences in survival after lobectomy and pneumonectomy only for patients who did not develop necrosis in primary tumor (р=0,17). Another morphological factors (histologyc form, morphologic differentiation, presents of visceral pleura infiltration) had no influence to survival of patients with lobectomy and pneumonectomy. Conclusions: Patients with I-II stages of non-small cell lung cancer after lobectomy had significantly better survival than patients after pneumonectomy (р=0,007). The worse survival time was detected in patients with following factors: female sex, II stage of disease, BMI <30 mg/m2, peripheral location of the primary tumor and presents of necrosis in the malignance. It is necessary to carry out future investigations to assess the effectiveness of additional treatment for patients with aggressive prognosis.
Эффективность хирургического лечения больных с I-II стадиями немелкоклеточного рака легкого
Effectiveness of surgical treatment of patients with non-small cell lung carcenoma I-II stages
Keywords: недрібноклітинний рак легені; прогноз; виживання; хірургічне лікування; клініко-морфологічні фактори; немелкоклеточный рак лёгкого; выживаемость; хирургическое лечение; клинико-морфологические факторы; non small cell lung cancer; prognosis; survival; surgical treatment; clinico-morphologycal factors